Human papillomavirus vaccination coverage among young, gay, bisexual, and other men who have sex with men and transgender women — 3 U.S. cities, 2016–2018. Issue 12 (2nd December 2021) - Amiling, Raiza; Winer, Rachel L.; Newcomb, Michael E.; Gorbach, Pamina M.; Lin, John; Crosby, Richard A.; Mustanski, Brian; Markowitz, Lauri E.; Meites, Elissa
ABSTRACT: Gay, bisexual, and other men who have sex with men (MSM) and transgender women are disproportionately affected by human papillomavirus (HPV). HPV vaccination is routinely recommended for U.S. adolescents at age 11–12 years, with catch-up vaccination through age 26 years. We assessed HPV vaccination coverage and associated factors among young MSM and transgender women. The Vaccine Impact in Men study enrolled MSM aged 18–26 years from clinics in Seattle, Chicago, and Los Angeles, during February 2016–September 2018. Participants self-reported socio-demographic information and HPV vaccination status. Among 1416 participants, 673 (47.5%) reported ≥1 HPV vaccine dose. Among vaccinated participants, median age at first dose was 19 years and median age at first sex was 17 years; 493 (73.3%) reported that their age at first dose was older than their age at first sex. There were significant differences in HPV vaccination coverage by city (range 33%–62%), age, race/ethnicity, and gender identity. Coverage was highest in Seattle, where younger age was the only factor associated with vaccination. Differences in coverage by city may be due to variation in vaccination practices or enrollment at study sites. Increasing both routine and catch-up vaccination will improve coverage among MSM and transgender women.